2022
DOI: 10.1002/adma.202108435
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Activation of TRPV1 Channels on Microglia to Boost Their Autophagy for Clearance of Alpha‐Synuclein and Enhance Therapy of Parkinson's Disease

Abstract: α-syn can spread through the adjacent neurons in anatomically connected brain regions, and serve as seeds to induce the aggregation and deposition of α-syn monomers, [3][4][5] which could increase oxidative stress, depolarize mitochondria, disturb protein clearance, and alter the cytoskeleton, leading to neuronal damage and the progression of PD. [6] The accumulation of α-syn in the midbrain plays a key role in the pathogenesis of PD, [7] and how to eliminate α-syn aggregates is crucial for the success of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 51 publications
0
53
0
Order By: Relevance
“…Studies have been reported on alleviating neurological diseases by regulating ROS or Ca 2+ , and we found that simultaneous regulation of ROS and Ca 2+ is a more efficient approach for alleviating neuroinflammation. Aβ42 aggregation produces excessive ROS, and Ca 2+ -permeable transient receptor potential melastatin-related 2 (TRPM2) ion channels are highly sensitive to ROS, resulting in abnormally elevated intracellular Ca 2+ concentration and activation of downstream neuroinflammatory signaling pathways .…”
Section: Introductionmentioning
confidence: 65%
“…Studies have been reported on alleviating neurological diseases by regulating ROS or Ca 2+ , and we found that simultaneous regulation of ROS and Ca 2+ is a more efficient approach for alleviating neuroinflammation. Aβ42 aggregation produces excessive ROS, and Ca 2+ -permeable transient receptor potential melastatin-related 2 (TRPM2) ion channels are highly sensitive to ROS, resulting in abnormally elevated intracellular Ca 2+ concentration and activation of downstream neuroinflammatory signaling pathways .…”
Section: Introductionmentioning
confidence: 65%
“…All data were statistically analyzed, and statistical significance was calculated via Student’s t -test or the log-rank (Mantel–Cox) test using GraphPad Prism 5 as described elsewhere. , A P -value <0.05 was considered statistically significant. * p < 0.05, ** p < 0.01, *** p < 0.001, **** p < 0.0001; ns, not significant.…”
Section: Methodsmentioning
confidence: 99%
“…Electron microscopy showed that claudin‐5, occludin, and ZO‐1 decreased after sonication in rats, and gradually returned to presonication levels (Liu, Gong, et al, 2020). Ultrasound‐mediated BBB opening has been applied to deliver conventional chemotherapeutic drugs and nanoparticles for the treatment of malignant gliomas and metastatic brain tumors (Liu, Ren, et al, 2019; Liu, Wu, et al, 2019; Ren et al, 2020; Wang, Zhang, et al, 2022; Xu et al, 2022; Yuan et al, 2022; Zhang et al, 2018).…”
Section: Bbb Alteration In Brain Diseases and Targeting Delivery Stra...mentioning
confidence: 99%